IMPLEMENTASI PROGRAM KARTU JAKARTA PINTAR DI DKI: PELUANG DAN TANTANGAN DALAM PEMENUHAN KEADILAN SOSIAL DI BIDANG PENDIDIKAN - Anggi Afriansyah (Research Centre for Population, Indonesian Institute of Sciences, 2017)
Jakarta Smart Card (KJP) is a program by the DKI Jakarta Provincial Government which gives a chance for the less affluent to achieve up to secondary education. This paper examines three aspects of KJP implementation, namely (i) opportunities and challenges of the program implementation as the fulfillment of social justice in education; (ii) problems related to the program implementation and its future challenges; and (iii) KJP as an effort to improve education services. This study used primary data obtained from interviews and relevant secondary data. The main finding indicates that violations and misuse of KJP fund still exist. Although the government has improved the rules, management, and mechanisms for the distribution of the program, inaccuracies in data and fund recipients are still found. Therefore, these issues need to be the points of evaluation, improvement, and innovation to fulfill the social justice for the disadvantaged citizens.